Understanding ideological diversity within China's emerging middle class - Kutarna, C (2015)
The Party-state's popular legitimacy is difficult to assess. This study aims to do so via a two- step methodology that aims to reveal the political belief sets through which the Chinese public evaluates the present regime and imagines possible alternatives. I focus upon the emerging middle class, as conceptualized by the Party-state, because the Party-state views this segment's support as a priority for its legitimation efforts. And I focus upon Beijing, because theory and evidence suggests that Beijing's emerging middle class should be especially persuaded by the Party-state's ideological work. Ideological diversity discovered in Beijing is a baseline of what one would hypothesize to exist elsewhere in China. First, I distil the main ideological traditions to which the emerging middle class is exposed— including Official Ideology, Liberalism, New Left and Political Confucianism—down into their essential convictions. Second, via Q Methodology, I present statements representing these distilled convictions to a sample of the emerging middle class and ask them, using these statements, to answer: 'What should the guiding values and principles of Chinese politics be?' From the patterns of their responses, I elucidate the variety of ways they evaluate the question—and hence, evaluate the legitimacy of the present regime. Four discourses emerge. Social Welfarism and Liberal Idealism form orthogonal boundaries between which most members of the emerging middle class situate themselves. Regression analysis suggests that the former is the default view, but a variety of factors can rotate people toward the latter. Authoritarian Reformism and Critical Realism are minority discourses that reveal more radical possibilities. My research suggests that the Party-state's efforts to contain public conceptions have had mixed success. The range of public political preferences is sufficiently constrained that a single Party can coherently claim to represent their fundamental shared interests. A corollary finding is that the 'middle class' is emerging into the role the Party-state envisages for it, as a stabilizing force. However, while its members may be 'allies of the state', only some are devotees, in the sense that they share substantially in the Official Ideological perspective. The bounded diversity of ideological discourses reveals the exquisite complexity of the Party-state's legitimation task, and many potential pitfalls and missteps. The present study reveals both the reach of the state (i.e., a bounded discourse weighted toward a Social Welfarist default) and its limits (i.e., popular drift toward problematic alternatives). More broadly, I find that popular legitimacy can be subjected to direct investigation. I show that while state-centric approaches to investigating China are compelling for their explanatory power, a balanced approach offers richer insight.